Manajemen Public Relations Melalui Media Internal “Milis Broadcast“ dalam Menjali Hubungan Harmonis dengan Karyawan Kantor Pusat PT. KAI (Persero) - Anggitia, Nadya; Suherdiana, Dadan; Paryati, Paryati (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2022)
This research aims to to find out the stages carried out by Public Relations Management through the Internal Media "Mailing List Broadcast" in Establishing Harmonious Relationships with Employees of the Head Office of PT KAI (Persero) in running the program held `through Mailing List Broadcast from planning, organizing, actuating, and controlling. This research uses a qualitative approach with descriptive research. This research uses POAC theory which describes the stages in establishing harmonious relations with employees of the head office of PT KAI (Persero). The results of this study indicate that the management of Public Relations through Mailing Lists Broadcast which includes planning, organizing, implementing and supervising. The first focus, planning (planning) carried out by the Head Office of PT. KAI (Persero) with the intention of determining the relationship between employees and the public. In public relations management, internal media such as mailing lists have a crucial role in establishing harmonious relationships with employees at the Head Office of PT KAI (Persero). Through planning, organizing, implementing and monitoring can make communication well established for internal audiences more effectively and efficiently.